2008
DOI: 10.1016/s0022-5347(08)61817-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer to Mouse Testes by Electroporation and Its Influence on Spermatogenesis

Abstract: We transferred the adventitious gene pCAGGS-lacZ to mouse testes with the use of a square-wave electroporator and investigated the efficiency of gene transfer (GT) and the influence of the procedure on testicular damage and spermatogenesis. Mice were divided into 5 groups: (1-2) injection of gene/phosphate-buffered saline (PBS) into the interstitial space followed by electroporation (EP), (3) EP alone, (4-5) injection of gene/PBS without EP. The presence of the lacZ gene was determined by X-gal (5-bromo-4-chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This increase in transfection efficiency 12,13,15 by elevated voltage is accompanied by the adverse effect of testicular shrinking [12][13][14] . The most favorable voltage range seems to be between 30-50 V, guaranteeing small effects upon testicular integrity, a normal sperm quality 16 , a normal mating behavior 17 , the maintenance of offspring production ability [16][17][18][19][20] as well as a sufficient transfection efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in transfection efficiency 12,13,15 by elevated voltage is accompanied by the adverse effect of testicular shrinking [12][13][14] . The most favorable voltage range seems to be between 30-50 V, guaranteeing small effects upon testicular integrity, a normal sperm quality 16 , a normal mating behavior 17 , the maintenance of offspring production ability [16][17][18][19][20] as well as a sufficient transfection efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem of electroporation is that the electric pulses themselves could result in testicular damage. In our previous reports, the Johnsen scores were significantly decreased and apoptotic cells were significantly increased in the testis several weeks after in vivo electroporation (Umemoto, 2002. These results suggest that spermatogenic damage caused by electroporation itself could be important problems for clinical application.…”
Section: Electroporationmentioning
confidence: 54%
“…As a possible alternative and more effective method for generating transgenic mice, several researchers have attempted testis-mediated gene transfer using an in vivo electroporation method. After injection of exogenous DNA into the testis, the testes are held between a tweezer-type electrode, and square electric pulses are applied several times at 20-50 volts (Muramatsu, 1996(Muramatsu, , 1997Yamazaki, 1998Yamazaki, , 2000Umemoto, 2002. Expression of the exogenous gene was clearly observed in germ cells of seminiferous tubules 48 hours after transfecting the mouse testis by in vivo electroporation (Muramatsu, 1997).…”
Section: Electroporationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo gene transfer into the testis by EP has been put forward as a non-hormonal approach to study the testis and sperm function, and as a novel way of creating transgenic animals. [41][42][43] Selective inhibitors of ion channels could, in principle, inhibit sperm function and prevent fertilization. By applying the patch-clamp technique to mature human spermatozoa, Lishko et al 44 and Strunker et al 45 independently found that the Catsper ion channel of human spermatozoa is synergistically activated by elevation The results were represented as mean6s.e.…”
Section: Discussionmentioning
confidence: 99%